Universiti Pertanian Malaysia Cooperative Bhd. - Atan, Rohana (1982)
The cooperative form of business is currently gaining popularity as a major bussiness venture. It is conducive to a situation where the.no of shareholders is more than fifty one- However in term of leqal obligation, it comes under the discretion of the Ministry of National and Rural Development where as the other form of business come under the discretion of the Ministry of Finance. One of such cooperatives operating in Malaysia is the Universiti Pertanian Malaysia Cooperatives Bhd. which has been established since 1976 with the ultimate objective of venturing into business that can benefit its members. Despite its existance for over 5 years; the author feels that its achievement so far is less than encoraging in comparison to its counterparts such as University of Malaya Cooperative Bhd. This qualitative evaluation is based on the author's personal observation being in the service of the University since 1974, and also the popular talk among the other staffs of the University.